DETERMINING THE EFFECTIVENESS OF COMPREHENSIVE DIAGNOSIS OF CERVICAL PRECANCER AND CANCER (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Cervical cancer is the most common form of oncological pathology of the female reproductive system. In terms of incidence, cervical cancer ranks 7th among all malignant tumors and 3rd among malignant tumors in women (after breast cancer and colon cancer) and accounts for 9.8% [1,9]. In 2022, 527,624 cases of cervical cancer were registered worldwide [1,11], with 265,653 deaths. Mortality from cervical cancer ranks 9th among all malignant tumors and 2nd among epithelial malignant tumors of the female reproductive system [1,12]. Cervical cancer most often affects women under 35 years of age, often with a subsequent fatal outcome [3,13]. In Uzbekistan, the incidence of cervical cancer is growing annually, which indicates the inadequacy of measures related to the primary and secondary prevention of this disease. In 2019, 14.7 thousand patients with cervical cancer were registered in Uzbekistan. The mortality rate from cervical cancer in Uzbekistan in 2019 was 5.2 per 100,000 and is currently the leading cause of death among all women with cancer aged 15 to 40 years (±19.5). After 40 years, mortality from cervical cancer moves to 2nd place (9.7%) [1,5,9,10]. The survival rate of patients with cervical cancer depends primarily on the level of the healthcare system in different regions. In less socio-economically developed countries, cervical cancer is mostly diagnosed at a late stage of the disease, therefore, low survival rates are recorded. The 5-year survival rate among women diagnosed with late-stage cervical cancer is approximately 30% lower than in more developed countries [1,10]. Clinical symptoms in patients with cervical diseases are usually caused by the presence of combined uterine pathology (endo- and myometrium). The combination of uterine fibroids with adenomyosis and/or endometrial hyperplasia in patients with CIN III (47.6%) and cervical cancer (59.1%) (p < 0.05) is significantly more common than the combination with other cervical pathologies. This fact is apparently due to the mutually stimulating influence of pathological processes in the endo- and myometrium on the condition of the cervix, which is realized through the mechanisms of intercellular interactions of growth factors [15].